Current CML therapy: progress and dilemma - Hehlmann, Rüdiger (Leukemia, 2003)
Rarely has progress in treatment of leukemia been as dramatic and convincing as with the BCR-ABL tyrosine kinase inhibitor imatinib.1 Imatinib induces remissions of CML as fast as hydroxyurea, achieves rates of cytogenetic remissions that by far exceed those induced by interferon α and has a toxicity profile as favourable as that of hydroxyurea and much superior to that of interferon α.2 In addition, the causal approach of this new drug, which may well serve as a model for new treatment modalities in other neoplasias is reassuring.